Influence of Project Type, Location and Area towards Construction Delay: a Review on Significance Level of Delay Factors - Ramli, Mohd Zakwan; Malek, Marlinda Abdul; Hamid, Baizura; Roslin, Nursyadzatul Tasnim; Roslan, Mohd Eqwan Mohd; Norhisham, Shuhairy; Mohd, Mohd Firdaus (International Journal of Engineering and Technology, 2018)
Construction delay is something that is inevitable, which is why it is a global problem faced by the construction industry. This paper highlighted the characteristics that influenced construction delay but usually ignored in many researches. Project type, location, and area are the characteristics that are not concerned by many. Therefore, this study is reviewing literature in construction delay to find the significance of the influence of the mentioned characteristics. It was found that there is a significant influence of the project type and location towards construction delay problems, where different project type experienced different delay causes. This was probably due to different difficulties faced by each of project type. Project location characteristic also undergoes the same pattern; which is within the same region, the same pattern of major cause was identified. Meanwhile, the insignificant level of influence was identified for the construction area characteristic. This was probably due to the readiness and awareness of contractor regarding the site condition before the construction start. It is expected that this study will open up more discussions regarding these characteristics in the future.